Dataset: Mapping Online Business and Commitment: Insights from Global Scholarly Works - Regita Amanah Huzairin; Mochammad Tanzil Multazam (Proceedings of The ICECRS, 2022)
This data article presents the results of a search for scholarly works on online business and commitment using the Lens.org database. The data were collected by applying filters for document type and subject and exporting the resulting datasets to CSV and Bibtex files. The data were then analyzed and compiled using Zenodo.org. The data provide valuable insights into the contributions of different institutions, authors, fields of study, and countries to research on online business and commitment. The results show that the London School of Economics and Political Science is the institution that contributed the most data, with the field of political science being the most active area of research. The data also reveal that the United Kingdom is the country that provided the most data and that Springer Nature is the most prolific publisher of scholarly works on this topic. These findings can be useful for scholars, students, and practitioners interested in online business and commitment, and the data can be used for further research and experimentation. Highlights: The data article presents search results on online business and commitment from the Lens.org database. The data provide insights on institutions, authors, fields of study, and countries that contribute to research on the topic. The findings can be useful for scholars, students, and practitioners interested in online business and commitment, and the data can be used for further research and experimentation.